SINGO’S PUBLIC SERVICE INNOVATION TO ADDRESS THE CHALLENGES OF BUREAUCRACY IN PUBLIC SERVICE: A PARTNERSHIP BETWEEN THE MINISTRY OF HOME AFFAIRS AND NGO PARTNERS (Pena Cendekia Insani, 2026)
The COVID-19 pandemic accelerated the digitalization of public administration in Indonesia. This study examines the Sistem Informasi Ormas Asing (SINGO), a digital platform developed by the Ministry of Home Affairs to address administrative constraints in cooperation between local governments and foreign non-governmental organizations. This research employs an exploratory qualitative approach using in-depth interviews and document analysis, with data analyzed through thematic analysis and validated by source triangulation. The findings show that prior to SINGO, administrative processes such as the preparation of Annual Work Plans, reporting, and coordination with multiple local governments were conducted manually, creating inefficiencies and compliance burdens for partner organizations. The implementation of SINGO digitized these procedures, improving coordination efficiency, transparency, and accountability through integrated reporting and the documentation of best practices. Based on the public service innovation typology, SINGO can be classified as an externally oriented service innovation developed through collaboration with non-governmental partners. Despite challenges related to system features and institutional capacity, SINGO demonstrates strong prospects for sustainability as a digital governance innovation in managing government cooperation.